2017
DOI: 10.18203/2349-2902.isj20174518
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of animal bite victims and admission in general surgery department, in Southern Odisha: a cross sectional institutional study

Abstract: Background: Human rabies continues to be endemic in India and according to recent estimate 20,000 persons die of this disease every year. Hence this study was conducted to know the prevalence and pattern of animal bites during last one year and to determine the rate of admission in Department of Surgery.Methods: This study was conducted in the casualty, Department of Community Medicine, Department of Surgery at M. K. C. G. Medical College, Odisha, India between 1st April 2016 - March 31st, 2017. It was a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…They observed a significantly higher number of people in the older age group practicing the first aid with the recommended materials (soap water) or other detergents such as iodine constituents or according to their availability. A similar study in India [ 36 ] showed that a majority of participants, including senior citizens, would practice the recommended procedures (soap water) to clean the wound. This might be due to the differences in the community KAP level of both countries’ communities.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a significantly higher number of people in the older age group practicing the first aid with the recommended materials (soap water) or other detergents such as iodine constituents or according to their availability. A similar study in India [ 36 ] showed that a majority of participants, including senior citizens, would practice the recommended procedures (soap water) to clean the wound. This might be due to the differences in the community KAP level of both countries’ communities.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] (50%) from Nagpur, Pattanayak et al . [ 21 ] (6.1%) from Kolkata, Gogtay et al . [ 9 ] (2.7%) from Mumbai, and Sahu et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to Sibaprashad Pattanayak (2017), 8 conducted in the casualty, Department of Community Medicine, Department of Surgery at M. K. C. G. Medical College, Odisha, India between 1st April 2016 -March 31st, 2017. Out of 6242 animal bite cases, 4785 (76.66%) were bitten by dogs.…”
Section: Discussionmentioning
confidence: 99%